وقف النقود في الفقه الإسلامي - فاطمة الزهرة, مرغني (University of Eloued جامعة الوادي, 2017)
عالج هذا البحث موضوع وقف النقود في الفقه الإسلامي إذ أجاب على إشكالية: ما هو حكم وقف النقود في الفقه الإسلامي؟ وما هي صوره المعاصرة؟ وقسم البحث إلى ثلاثة مباحث، المبحث الأول وضح مفهوم الوقف وما يتعلق به، بينما عالج المبحث الثاني حكم وقف النقود في الفقه الإسلامي، وأما المبحث الثالث فتناول صور وقف النقود المعاصرة. وأهم النتائج المتوصل إليها: أن وقف النقود جائز ومشروع وهو من الأدوات المهمة التي يحتاج إليه بصفة خاصة في تسيير القرض الحسن، ويسهم وقف النقود في تدعيم الاستثمار ومحاربة الفوائد الربوية المسببة للأزمات الاقتصادية، و أكد البحث في توصياته على ضرورة نشر ثقافة وقف النقود في المجتمع. This research dealt with the issue of stopping money in Islamic jurisprudence, as he answered the problem: What is the ruling on stopping money in Islamic jurisprudence? And what is its contemporary image? The second section deals with the cessation of money in Islamic jurisprudence. The third section deals with the contemporary forms of monetary cessation. The main findings are that stopping money is permissible and legitimate. It is one of the important tools that are particularly needed in the management of the good loan. The suspension of money contributes to the promotion of investment and the fight against the interest of riba that causes economic crises. The research emphasized in his recommendations the need to spread the culture of stopping money in society .
مذكرة ماستر تخصص معاملات مالية
Keywords: وقف، النقود ، الفقه الإسلامي.; stood up، Money، Islamic Fiqh.